Poetry and freedom : discoveries in aesthetics, 1985-2018 - Oppenheimer, Paul, 1939-2022 ([Anthem Studies in South Asian Literature, Aesthetics and Culture], 2020)
This book offers a ground-breaking exploration of the aesthetics of poetic freedom. The range is broad, from antiquity to the present and from Europe and the Middle East into the poetry of the English-speaking world. Revealing questions about the elusiveness of poetic freedom-what does the term actually mean?-are repeatedly tested against the accomplishments of major poets such as Whitman, Dickinson, Rilke, Dante and Virgil, and their public yet intensely private originality. The result is a fresh, and well-nigh revolutionary, way of seeing literary and modern history, or an initiation into the more striking gift of aesthetic freedom.